Kolaborasi dan E-Literacy: Kunci Keberhasilan Inovasi E-Government Pemerintah Daerah: Collaboration and E-Literacy: Key Success Innovation of Local E-Government - Rozikin, Mochammad; Hesty, Wa; Sulikah, Sulikah (Pusjar SKPP Lembaga Administrasi Negara, 2020)
E-government is a type of bureaucratic reform which not only highlights technological changes but also changes in the government system involving citizens in policy decision-making. Human resources, leadership and community engagement are critical success factors for innovation in e-government. Therefore, a local government innovation strategy is essential to enhance e-government growth through collaboration and e-literacy. Collaboration is a mechanism of collaboration between one government agency and other governments to jointly solve problems. Although e-literacy is a human resource capability in the learning process to understand a media. The methodology used was library research using previous research articles, books and website literature related to e-government innovation. The stage of the e-Government innovation strategy can be clarified by implementing the SWOT analysis of internal factors such as strength and weakness and external factors, namely opportunities and threats to establish SO strategy, ST strategy, WO strategy and WT strategy. The stages of innovation can be done through two processes, namely collaboration and innovation. The mechanism of collaboration is carried out in order to overcome budgetary problems and to strengthen inter-related agencies in the development of e-government. The e-literacy process is conducted to enhance community participation and development of human capital through community socialization, training of trainers and comparative studies. Keywords: Collaboration, E-Literacy, Innovation, Local E-Government Abstrak E-government merupakan sebuah bentuk reformasi birokrasi yang tidak hanya menekankan, baik pada perubahan penggunaan teknologi, tetapi juga perubahan sistem pemerintahan dalam pelibatan masyarakat untuk pengambilan keputusan. Faktor-faktor penentu keberhasilan inovasi e-governement adalah sumber daya manusia, leadership, dan partisipasi masyarakat. Oleh karena itu, diperlukan sebuah strategi inovasi dari Pemerintah Daerah untuk meningkatkan pengembangan e-government melalui kolaborasi dan e-literacy. Kolaborasi merupakan suatu proses tindakan kerjasama antara satu instansi pemerintah dengan pemerintahan lainnya guna memecahkan masalah secara bersama-sama. Sedangkan e-literacy merupakan suatu kemampuan sumber daya manusia untuk memahami suatu media dalam proses pembelajaran. Metode yang digunakan adalah studi pustaka, baik menggunakan jurnal penelitian terdahulu, buku maupun web literature yang berkaitan dengan inovasi e-government Pemerintah Daerah. Tahapan strategi inovasi e-government dapat dijelaskan melalui pengembangan dari analisa SWOT terhadap faktor-faktor internal, yaitu kekuatan dan kelemahan dan faktor eksternal, yaitu peluang dan ancaman sehingga menghasilkan strategi SO, strategi ST, startegi WO, dan strategi WT. Tahapan inovasi dapat dilakukan melalui dua proses yaitu kolaborasi dan inovasi. Proses kolaborasi dilakukan untuk mengatasi masalah anggaran dan penguatan antar instansi terkait dalam pengembangan inovasi e-government. Proses e-literacy dilakukan untuk meningkatkan partisipasi masyarakat dan pengembangan sumber daya manusia dengan cara sosialisasi kepada masyarakat, training of trainers, dan studi banding. Kata kunci: Kolaborasi, E-Literacy, Inovasi, E-Government Pemerintah Daerah